Article 3 of the European Convention on Human Rights violations in detention places for asylum seekers - Zariņa, Roberta (Riga Graduate School of Law, 2020)
This paper examines Article 3 ECHR violations in asylum seeker detention places. This has been a topical issue for the last few years and will be further as asylum seekers are still an ongoing issue. The detention places are the most common place where asylum seekers are staying; thus, compliance with the law should be ensured. Especially, as Article 3 is one of the absolute and non-derogable rights, therefore, the compliance of it is necessary for every Council of Europe Member State. In the analysis part, the ECtHR case-law provides examples and further analysis of detention place conditions to see whether there are violations and to what extent. Possible reasons and preventive mechanisms are also analyzed in this thesis.